Comparison of Tramadol and Pethidine for Control of Shivering Following Central Neuraxial Blockade - Prameela VS; Madhu Kumar BS; Kumar, Brijesh (Academia Anesthesiologica International, 2020)
Background: Central neuraxial blockade is associated with shivering in 40-60% of the patients. A popularly used drug to control shivering is pethidine. The present study was conducted to evaluate the effect of tramadol on shivering and compare it with the efficacy of pethidine. The study was also intended to compare the haemodynamics, complications and recurrence of shivering with the use of pethidine and tramadol. Subjects and Methods: This prospective comparative study was conducted in Department of Anaesthesiology, Akash Institute of Medical Sciences and Research Centre, Devanahalli, Bengaluru. In this study, 80 consenting patients of either gender, aged between 20-60 years, in American Society of Anesthesiologists (ASA) Grades 1, 2 and 3 according to ASA who experienced shivering during or immediately after elective surgeries under central neuraxial blockade (spinal, epidural and combined spinal and epidural) were randomized to receive either pethidine 1mg/kg or tramadol 1 mg/kg for control of shivering. The time interval for the onset of shivering after regional anaesthesia, onset of disappearance of shivering after drug administration, complete disappearance of shivering, hemodynamics, recurrence of shivering and complications were recorded. Results: There was no statistical difference in the onset of disappearance between the 2 groups (p=0.615). Time taken for complete disappearance of shivering after 5 minutes interval period was statistically more in Group T (17.5% vs 5% in Group P) with p= 0.154. Recurrence of shivering occurred more in the tramadol group as compared to pethidine group which was strongly significant statistically (27.5% vs 5.0%) with p=0.006. However the incidence of complications was higher with pethidine with a greater drop in mean blood pressure, increased indicators of respiratory depression, more sedation, greater nausea, vomiting and itching. Conclusion: The present study results may conclude that tramadol is an effective drug in the control of shivering with more stable hemodynamic and fewer side effects such as sedation, respiratory depression, nausea, vomiting and itching. However one must be prepared for a slight delay in the onset of its action and expect a recurrence of shivering which may require further therapy. Pethidine, with its equal efficacy may be advocated in patients allergic to tramadol and where sedation is desirable.